POPULATION OF Hirundo rustica Linn. 1758 AND ITS DIET COMPOSITION IN BANDUNG AND CIANJUR, WEST JAVA - Jaelani, Achmad
H. rustica Linnaeus, 1758 is an insectivorous bird which migrated to Java Island. This migration occurs because of lack of food resources in the breeding area. Food availability in the migration destination area is one of the key factors for successful migration of H. rustica. How ever, information about how H. rustica used natural resources while living in destination area is still lack. This study aims to estimate population size, determine the composition and type of alimentary important, inventorize type of foods in the foraging area. This research was conducted in Bandung and Cianjur. Estimation of bird population was carried out by total count method using panoramic photograph. The composition and alimentary important were determined by analyzing of gizzard content. Inventorize Prey insects were sampled by using malaise trap. Population of H. rustica in Bandung was 7778 during October, while in Cianjur there were 14199 individuals in the same period. The population size was increased every month and reached its peak in December at 20880 individuals (Bandung), and 31944 individuals (Cianjur). Both populations numbers are the first record in the respective places. The highest important value index of diet (AIi) was recorded in Coleoptera group (9,5) in Bandung and in Hemiptera group (27,8) in Cianjur. Based on average numbers of prey insects per individual, the results in Bandung and Cianjur were significantly different (p<0,05). The coefficient of variation in both locations showed a high variation of prey types. Differences in important value index of diet and coefficient of variation in both locations showed that H. rustica utilized the abundance of insects in foraging area. The average of prey insects to population size show tha the prey insect negatively affect population size. Inventarization of prey insects in Bandung has recorded eight group of prey, three of them were not found in gizzard, while there were nine group of prey found in Cianjur, four of which were not found in gizzard. Both in Bandung and Cianjur were dominated by diptera (>50% and 48% respectively). The group of prey and the AIi index value indicating H. Rustica utilized efficiently of abundant and potential prey insects as source prior to return to the breeding area.